Erratum: Geometric Approach to Predator-Prey Model with Carrying Capacity on Prey Population - Marshellino; Tasman, Hengki; Rusin, Rahmi (The Indonesian Bio-Mathematical Society, 2025)
This erratum addresses inaccuracies found in the figure captions of the article titled